Digital Finance For Improving Financial Inclusion Indonesians’ Banking - Estu Widarwati; Asep Solihin; Nunik Nurmalasari (Signifikan: Jurnal Ilmu Ekonomi, 2022)
A digital finance service breakthrough is essential to get better financial assistance to optimize financial inclusion, and the effectiveness requires technological support in banking financial services. The study investigates the effect of digital finance on financial inclusion in Indonesians’ banking industry. We develop the new measurement, namely average digital finance (ADF), and use loan transactions to proxy financial inclusion. The samples are six banking during 2013-2019, and we use panel data regression to test the hypothesis and do a robustness check. Our result confirms that ADF positively impacts financial inclusion and finds evidence of bank size’s role in digital finance and financial inclusion. It implicates banks’ strategy for optimizing financial inclusion based on its characteristics such as age, profitability, and efficiency. It contributes to digital finance’s government policy for using explored internet banking and mobile banking stimulatingly.Widarwati, E., Solihin, A., & Nurmalasari, (2022). Digital Finance For Improving Financial Inclusion Indonesians’ Banking. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 17-30. https://doi.org/10.15408/sjie.v11i1.17884.